The relationship between personality, work-life balance, burnout and individual work performance among Royal Customs Officers in Kuching, Sarawak / Eveana Crystle anak Peng Guan...[et.al] - Penguan, Eveana Crystle; Awang, Jacqueline Carrie; Anjemeh, Laura A. (2018)
The purpose of this study is to examine the relationship between personality, work-life balance, burnout and individual work performance among Royal Customs Officers working in Kuching, Sarawak. It aims to investigate the personality types, level of work life balance and burnout and their correlation to individual work performance. Three research questions and ten hypotheses are developed to study the correlation between personality, work life balance and burnout and individual work performance via correlation analysis. A total of 312 sets questionnaire were distributed for the purpose of the present study. Based on the feedbacks from the usable 300 respondents, the study reveals that there is a positive or negative correlation between personality, work life balance, and burnout and individual work performance. This findings of the present study encourage further examinations of work-family conflict and the additional research may provide a greater understanding of the phenomenon. It is hoped that the information gleaned from the present study will assist the Royal Customs in Kuching, Sarawak in designing appropriate policies and awareness programs related to individual work performance.